Implementasi Jaringan Komputer Thin client Ncomputing Vspace Type L130 (Yayasan Kawanad, 2022)
This paper discusses the concept, implementation and performance testing of thin client networks based on terminal dumps and diskless. By applying the distributed dump terminal and diskless thin client method, to access all web-based applications implemented at the STMIK Indonesia computer laboratory in Banda Aceh to increase effectiveness and efficiency in centralized data processing on the server. From the results of the installation and testing carried out, it can be concluded that; Testing the effectiveness of Ncomputing devices is carried out on the CPU, RAM, and network traffic, as well as PF-RAM which can show the performance of computer access. The results of the test experiment show that with the Host specification P4 Core2 duo 3 GHz with 1 GB RAM and the Windows XP service pack operating system. 2 for 10 clients will be effective if the host and client each use 1 application, If the specifications above, RAM is upgraded by 4 GB and the operating system uses windows 2000/2003 server and linux with a special type, will be effective for clients with 30 users if applications that are used to host a maximum of 1 application and a client 2 spread sheet applications, Thin client distributed dump terminal and diskless can run using one server and ten users only use NComputing devices with supporting devices, namely display or monitor, mouse and keyboard, which are connected to the host via network cable, and all users can be managed by one server er and all data in the topology is only on the server.